Stroke Severity and Level of Dependence Against Risk of Falls in Stroke Patients - Puji Astuti Wiratmo; Sandi Irvanta; Sari Narulita (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
A stroke is a neurological disease caused by the blockage or rupture of blood vessels in the brain. Functional dysfunction due to stroke causes stroke patients to be very susceptible to falls. This research aimed to identify the association between the severity of stroke with the level of patient dependence on the risk of falls. This research was a quantitative observational design with a cross-sectional approach. The sample of this study was 66 hospitalized stroke patients who were recruited by quota sampling method. The National Institute of Health Stroke Scale (NIHSS) and Barthel Index are used to measure stroke severity and level of dependence. We assessed the risk of falls using the operational procedure from the hospital. Based on the Spearman rho test, it is found that there is a significant relationship between stroke severity and the level of risk of falls (p=0.000394). Similarly, a significant correlation was found between the level of patient dependence and the level of risk of falls (0.000016). Nurses need to set the nursing care plan for stroke patients who are at risk of falls to prevent further injuries and complications. Continuity of care and family support will help the patient's dependency, reduce the risk of falls, and promote quality of life.